Preparation and characterization of the PLA: GA: ZnO nanofibers-based drug delivery system - Ghadeer Ihsan Ali; Salih Abbas Habeeb (Results in Chemistry)
The production and development of drug-loaded nanofibers by electrospinning are interesting because of their use as scaffolds in drug-delivery system applications. In the present study, preparing the 50:50 polylactic acid: Gelatin and ZnO nanoparticles (PLA: GA: ZnO) scaffold nanofibers for loading the anti-inflammatory drugs naproxen and meloxicam at 0.1, 0.2, and 0.3 wt% of each drug. The morphology results measured by scanning electron microscopy showed significantly increased diameters by 556 ± 427, 566 ± 437, and 1298 ± 723 nm for 0.1 %, 0.2 %, and 0.3 wt% for naproxen, respectively, compared with 352 ± 245 nm for PLA: GA: ZnO. While the meloxicam revealed nanofibers with smaller diameters, the respective diameters for the ratios 0.1 %, 0.2 %, and 0.3 % were 327 ± 163 nm, 312 ± 156 nm, and 333 ± 209 nm. Zinc oxide increases the crystal size, while the loaded drugs improve the degree of crystallization. Consequently, the fibers turn into a low-crystalline structure. FTIR spectroscopy results indicated no chemical interaction between the polymers. Moreover, adding zinc oxide nanoparticles to the blend polymer fibers increased the surface's free energy by 56.31 ± 1.69 mJ.m−2 and reduced the contact angle to 83.16 ± 2.49°. Conversely, both naproxen and meloxicam increased the contact angle and reduced the surface's free energy, reaching values of 116.14 ± 3.48°, 114.4 ± 3.43°, 37.05 ± 1.11 mJ.m−2, and 38.78 ± 1.16 mJ.m−2. In addition, the drugs accelerate the thermal degradation of the polymer matrix. Mechanical properties as maximum tensile strength, were enhanced by ZnO nanoparticles (Q2), increasing by 3.62 % compared to Q1. However, naproxen or meloxicam deteriorate these properties by disrupting the structural integrity of the polymer matrix by 1.6 % and 4.21 % for Q3 and Q4 compared to Q1. The maximum cumulative release for drug samples at 21 days was 97.62 ± 4.88 %, and 93.75 ± 4.53 % for NAP and MEL, respectively, while 87.24 ± 4.24 % for PLA: GA: ZnO. The kinetic model for samples showed the Korsmeyer-Peppas more suitable in this study; the burst release of 60.66 % and 55.67 % drugs from NAP and MEL nano-fibrous formulations was observed during the first 24 h. All nanofiber samples' diffusion coefficient (n) values were n < 0.45, confirming that the drug release mechanism follows Fickian diffusion. Naproxen produced a diameter of inhibition zones (MIC) at a stock solution (MIC1000) of 17 ± 3.7 mm against S. aureus and 16 ± 3.1 mm against E. coli, while meloxicam showed MIC1000 of 18 ± 3.4 mm and 17 ± 3.7 mm against S. aureus and E. coli, respectively. All dilution ratios of the drug solutions showed antibacterial activity. All samples showed no cytotoxicity, with cell viability ranging from 81 % to 98.5 %, confirming their biocompatibility. In addition, the naproxen showed a low half-maximal inhibitory concentration (IC50) value, indicating that the drug is effective at low concentrations. The PLA: GA: ZnO nanofibers as effective carriers for sustained drug delivery, combining favorable mechanical properties, controlled release, and antibacterial efficacy. The statistical analysis of all samples (P < 0.05).